Đánh giá thực trạng hỗ trợ học tập cá nhân hóa cho sinh viên tại hai trường đại học thành viên thuộc Đại học Quốc gia Hà Nội - Nguyễn, Hòa Huy (Tạp chí Giáo dục, 2024)
Personalization has become an inevitable trend in all areas of life and education is also one of them. Personalized learning is a basic requirement of education 4.0, considered an educational method focusing on the needs, interests, goals and abilities of each learner. To assess the current situation of personalized learning support for students at Vietnam National University, Hanoi, the study collected survey responses from 400 students of two member universities, VNU University of Education (UEd) and University of Engineering and Technology (UET). The results show that there are five influential factors in supporting personalized learning for students, in descending order: (1) Learning support from instructors, (2) learners’ goals and progress, (3) Learners’ right to make choices about their learning, (4) Use of technology to access and support learning, (5) The connection of homework. The findings are considered a useful reference for managers in improving the effectiveness of personalized learning at universities in general and Vietnam National University, Hanoi in particular.